Frequency of Obstetrical Hysterectomy in Morbidly Adherent Placenta in Women with Previous Cesarean Section in Tertiary Care Hospital - Fahmida Parveen, Samia Aijaz, Wasfa Aijaz, Naila Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of obstetrical hysterectomy in the morbidly adherent placenta in women with previous cesarean sections in tertiary care hospital. Study design: A cross-sectional study Place and Duration: Gynecology and obstetrics department of Liaquat university hospital Hyderabad from 5th November 2020 to 5th May 2021 Methodology: This study comprised 62 women who had placentas that were identified as morbidly adherent by Doppler ultrasound. Repeat ultrasound scans were used to monitor cases with grossly adherent placentas. The condition of the mother and fetus was routinely evaluated in the hospital, where blood was cross-matched for transfusion. All information was entered into a pre-made proforma. Results: The women were 30.68 ±4.70 years of age on average. When a placenta was morbidly adherent and in a woman who had previously had a caesarean section, 7.41% (17/62) of those women underwent an obstetrical hysterectomy. These women spent an average of 4.92 ±2.65 days in the hospital. Conclusion: - In 7.41% of cases, obstetrical hysterectomy was performed on women who had previously undergone caesarean section because of a morbidly attached placenta. These findings suggest that a morbidly adhered placenta can seriously interfere with a female’s ability to procreate. It is crucial to make a well-informed decision about having a C-section in the first place, and following previous C-sections, vaginal birth should be given some thought. Keywords: caesarean section, morbidly adherent placenta, hysterectomy